2007
DOI: 10.1105/tpc.106.048744
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Visualization of Mg-ProtoporphyrinIX, a Coordinator of Photosynthetic Gene Expression in the Nucleus and the Chloroplast

Abstract: The photosynthetic apparatus is composed of proteins encoded by genes from both the nucleus and the chloroplast. To ensure that the photosynthetic complexes are assembled stoichiometrically and to enable their rapid reorganization in response to a changing environment, the plastids emit signals that regulate nuclear gene expression to match the status of the plastids. One of the plastid signals, the chlorophyll intermediate Mg-ProtoporphyrinIX (Mg-ProtoIX) accumulates under stress conditions and acts as a nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
103
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(112 citation statements)
references
References 54 publications
6
103
3
Order By: Relevance
“…Each enzymatic step involved in porphyrin synthesis is tightly regulated to avoid the phytotoxic accumulation of intermediates while ensuring sufficient enzymatic capacity and continuous cofactor supply to the cognate apoproteins (Tanaka and Tanaka, 2007). The latter is exemplified by the coordination of chlorophyll synthesis with the production of lightharvesting chlorophyll proteins (Lhcs) encoded by the nucleus, which is in part mediated by retrograde signals from the chloroplast to the nucleus (Strand et al, 2003;Nott et al, 2006;Ankele et al, 2007). In addition, tetrapyrrole synthesis and degradation are carefully adjusted to the cellular requirements, reflecting the different needs under varying environmental conditions Tewari and Tripathy, 1998;Wilson et al, 2003).…”
mentioning
confidence: 99%
“…Each enzymatic step involved in porphyrin synthesis is tightly regulated to avoid the phytotoxic accumulation of intermediates while ensuring sufficient enzymatic capacity and continuous cofactor supply to the cognate apoproteins (Tanaka and Tanaka, 2007). The latter is exemplified by the coordination of chlorophyll synthesis with the production of lightharvesting chlorophyll proteins (Lhcs) encoded by the nucleus, which is in part mediated by retrograde signals from the chloroplast to the nucleus (Strand et al, 2003;Nott et al, 2006;Ankele et al, 2007). In addition, tetrapyrrole synthesis and degradation are carefully adjusted to the cellular requirements, reflecting the different needs under varying environmental conditions Tewari and Tripathy, 1998;Wilson et al, 2003).…”
mentioning
confidence: 99%
“…This includes the retrograde signaling pathways between chloroplast and nucleus (Ankele et al, 2007;Koussevitzky et al, 2007). Similarly, mitochondrial retrograde regulation has recently been highlighted (Rhoads and Subbaiah, 2007) and also shown to play a key role in maintaining cellular homeostasis (Noctor et al, 2007).…”
mentioning
confidence: 99%
“…On the other hand, fundamental roles of tetrapyrrole intermediates in plastid-to-nucleus signaling pathways have been proposed, according to the fact that gene products of the other four GUN loci (gun2-gun5) have been identified as catalytic enzymes or interaction cofactors for tetrapyrrole biosynthesis in Arabidopsis (Susek et al, 1993;Mochizuki et al, 2001;Larkin et al, 2003). Although several research groups suggested that Mg-proto IX was essential as the signaling molecule of this pathway (Strand et al, 2003;Ankele et al, 2007), recent work found no correlation between steady-state levels of Mg-proto IX and transcription activities of nucleusencoded genes (Mochizuki et al, 2008;Moulin et al, 2008). Recently, it was demonstrated that heme, another tetrapyrrole intermediate, modulated the expression of nuclear genes in a similar manner to Mgproto IX in Chlamydomonas reinhardtii (von Gromoff et al, 2008) and Arabidopsis (Woodson et al, 2011).…”
Section: Discussionmentioning
confidence: 99%